IMPLEMENTASI PERATURAN OTORITAS JASA KEUANGAN (POJK) DALAM MENGAWASI PINJAMAN ONLINE PADA KANTOR OJK REGIONAL 8 BALI DAN NUSA TENGGARA - Ni Kadek Duwi Kumala Sari; Ni Wayan Suartini; I Nyoman Gede Supraptha (Nusantara Hasana Journal, 2022)
The problem of online lending or Peer to Peer Lending which continues to be in the public spotlight day has resulted in huge losses for the community, especially in the midst of the Covid-19 pandemic situation.This study aims to describe the Laws and Regulations and Supervision of the Financial Services Authority and their effect on the development of Online Loans in Bali Province. The method used in this study is a quantitative descriptive research method. Where secondary data from laws and regulations, books, and primary data obtained from questionnaires. The results of this study show: (1) Laws and Regulations have a positive and significant effect on Online Loans, significance value of 0.000 was obtained with a coefficient value of 0.449. (2) Supervision has a positive and significant effect on Online Loans, a significance value of 0.000 with a coefficient value of0.530 is obtained. (3) Laws and Regulations and Supervision simultaneously have a positive and significant effect on Online Loans, a significance value of 0.000 was obtained.